The Role Of Syekh Haji Bahauddin Tawar In Islamic Education In Aceh Singkil - Mukhlis, Mukhlis; Mukti, Abd.; OK, Azizah Hanum (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to determine the role of Sheikh Haji Bahauddin Tawar in the implementation of Islamic education in Aceh Singkil. This research method uses a qualitative approach and the focus in this research is discussing character study research. Data collection for this research was obtained using participant observation, interviews and study techniques. documents. Analysis of this research data was obtained using data reduction techniques, data presentation, and drawing conclusions. The results of the research revealed findings that the development of the Islamic Education institution founded by Sheikh Haji Bahauddin Tawar in Aceh Singkil has developed well. The efforts made by Sheikh Haji Bahauddin Tawar in the Islamic Education Institution in Aceh Singkil are: 1. Managing the Darul Muta'allimin Islamic boarding school well 2. Establishing educational institutions in villages in collaboration with the local community 3. Sending students to become teachers’ educators to villages 4. Inviting the community to provide an understanding of how important Islamic religious knowledge is in religious dialogue and lectures 5. Fostering the community through the forum of Tarikat (persulukan) 6. Conveying da'wah through the practice of five daily prayers and the Prophet's salawat and Islamic poetry. There is a very close connection between the educational institution founded by the students of Sheikh Haji Bahauddin Tawar and the thoughts and ideas of Sheikh Haji Bahauddin Tawar which played a role in the implementation of Islamic religious education and the institution he founded, namely the Darul Muta'allimin Tanah Merah Islamic boarding school.